The Role of the Application of Periphrases in the Folk Proverbs Built on the Base of Minerology Terminology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the folk proverbial periphrases that are based on mineralogy terminology. On the ground of the given samples we tried to clarify that the exquisite periphrases used in the proverbs help to enhance their artistic quality and reinforce their message while maintaining each image's clarity.